PENGARUH JOB CRAFTING TERHADAP WORK ENGAGEMENT YANG DIMEDIASI OLEH PERSON JOB FIT PADA PT. BERLIAN JASA TEMINAL INDONESIA - FATTI FAZRIATI, NUR (Jurnal Ilmu Manajemen (JIM), 2017)
Work engagement in a job is a must for employees. It is influenced by many factors, and of course, that factor is something that supports their comfortability in working and facilitating in facing job challenge. This study aims to determine the effect of job crafting on work engagement mediated by person job fit at PT. Berlian Jasa Terminal Indonesia. The type of this research is quantitative with sampling method used is random sampling with the number of samples 93 respondents. Analysis method using partial least square (PLS). The results of this study indicate that Job crafting has no effect on work enggement at PT. Berlian Jasa Terminal Indonesia, while job crafting has an effect on person job fit . The results of this study also showed that person job fit influenced work engagement, and Person job fit was able to mediate the influence of job crafting on work engagement. Based on the results of this study is the company expected to always their employee to increase job crafting that can cause comfortability in the process of working. Keywords: Job crafting, Person job fit, Work engagement